1995
DOI: 10.1172/jci118211
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclooxygenase-2 in human umbilical vein endothelial cells by lysophosphatidylcholine.

Abstract: Lysophosphatidyicholine (lysoPC), a component of atherogenic lipoproteins and atherosclerotic lesions, has been recently suggested to play a role in atherogenesis. LysoPC is known to induce several endothelial genes involved in leukocyte recruitment, mitogenesis, and inflammation. Cyclooxygenases (prostaglandin H2 synthases) are rate-limiting enzymes involved in the endothelial synthesis of prostacyclin, an antiplatelet, vasorelaxant, and vasoprotective molecule. We investigated the effect of lysoPC on the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 46 publications
5
47
1
1
Order By: Relevance
“…As shown in Fig. 3, no mobility shift of ERK2 was observed in cells treated with different concentrations of lyso-PC (1, 10, and 20 M) for different intervals (5,10,15,20, and 25 min). In contrast, such a mobility shift was readily detected in the cells treated with known MAPK stimulators, TPA and lyso-PA.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…As shown in Fig. 3, no mobility shift of ERK2 was observed in cells treated with different concentrations of lyso-PC (1, 10, and 20 M) for different intervals (5,10,15,20, and 25 min). In contrast, such a mobility shift was readily detected in the cells treated with known MAPK stimulators, TPA and lyso-PA.…”
Section: Resultsmentioning
confidence: 73%
“…The addition of lyso-PC to cultured cells can transcriptionally up-regulate the expression of a variety of genes including cell adhesion molecules (intercellular adhesion molecule 1 and vascular cell adhesion molecule 1) (10), growth factors (platelet-derived growth factors A and B and heparin-binding epidermal growth factor) (11,12), and vasoprotective enzymes such as nitric-oxide synthase (13,14) and cyclooxygenase-2 (15). In vascular smooth muscle, lyso-PC has been shown to induce vascular relaxation (16,17) and to stimulate cell proliferation (18,19).…”
mentioning
confidence: 99%
“…5,[24][25][26][27][28] In VSMCs, lyso-PC has been shown to be toxic to cells at high concentrations while lower concentrations induce DNA synthesis and cell growth, which over a narrow concentration range can cause both cytotoxic and proliferative effects. 7,11) Several investigators have reported that G protein-mediated signal transduction is impaired by high levels of lyso-PC.…”
Section: )mentioning
confidence: 99%
“…44 Several research groups have demonstrated that LPC alters various endothelial functions and induces several endothelial genes expressed in the atherosclerotic arterial wall. Reports describe the induction of intracellular adhesion molecule-1, macrophage chemoattractant protein-1, cyclooxygenase-2, and growth factors in endothelial cells, 16,17 possibly through modulation of transcription of nuclear factor B via a protein kinase C-mediated pathway. 45 However, some reports suggest that Ox-LDL has opposing effects on the activities of transcription factor activator protein-1, suggesting involvement of mechanisms for transcriptional regulation that are strongly affected by oxysterols rather than LPC.…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylcholine (LPC) has been reported to mediate several of the proinflammatory effects of oxidized LDL (Ox-LDL), to stimulate smooth muscle cell proliferation, and to induce several endothelial genes expressed in the atherosclerotic arterial wall. 16,17 LPC, which has also been identified in experimentally induced atherosclerotic lesions in animals, has been shown to be chemotactic. 18 Albumin represents the most abundant serum protein, with normal concentrations lying between 35 and 50 g/L.…”
mentioning
confidence: 98%